Self-medication in the pandemic period of COVID-19: Integrative review (Research, Society and Development, 2021)
Sars-CoV-2, Coronavirus or COVID-19, is a viral spectrum respiratory syndrome first evidenced in December 2019 in Wuhan, China. Because it is still a little known virus with lethal potential, the population seeks to find a quick and easy solution to the disease, such as the practice of self-medication. The object was to write the factors that corroborate the practice of self-medication in a covid-19 pandemic period. This is an integrative review of the literature, where the construction of the study was based on the question "What factors corroborate the practice of self-medication in a period of COVID-19 pandemic?". The bibliographic survey was carried out in February 2021, using the Medline, PubMed, Redib and Scielo databases using the descriptors "Self-medication", "Coronavirus Infections", "Health Education". After the inclusion and exclusion criteria, 6 articles with an adequate profile for the production of this study remained. The articles showed that self-medication was promoted in the pandemic period, being used both for prevention and treatment of COVID-19. The irrational use of medicines has taken on the side of the alleged treatments related to COVID-19.